PENERAPAN MODEL PROBLEM BASED LEARNING UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK KELAS 4 SD KATOLIK SANTA ANGELA PADA MATERI GAYA DI SEKITAR - Maria Adik Purwita Budi Utami; Yuni Gayatri; Ni Luh Putu Sari Murthi (Universitas Muhammadiyah Surabaya, 2024)
This study aims to improve the learning outcomes of class IV-A students at SDK Santa Angela through the application of the Problem Based Learning model on the material of forces around. The type of research used is pseudo-experimental research. The research design is one group post test only control group design. The subjects of the research conducted were class IV-A students of SD Katolik Santa Angela, totaling 20 people in the 2023/2024 school year. Data collection techniques by means of observation and tests. The research instruments used observation sheets of learning implementation, attitude observation sheets, skill observation sheets and cognitive test sheets. Data analysis was carried out by descriptive statistics and qualitative. The results of this study show that all stages of Problem Based Learning are well implemented. The results of the observation of the attitude of students show that 100% of students meet KKTP, the results on the skills aspect in presenting show 100% of students meet KKTP, and learning outcomes in the knowledge aspect show 85% meet KKTP. The results of the reflection showed that all students felt happy and could understand the material taught. The conclusion of this study is that the application of the Problem Based Learning model effectively improves student learning outcomes.